Vanadium-Lead Doped Bi-2223 Superconductor - Supreya Trivijitkasem,; Chirawat Kluenrat,; Viboon Pumchuchit, (Agriculture and Natural Resources, 2006)
The effect of vanadium-lead doped in Bi-Sr-Ca-Cu-O superconducting system was studied. A series of initial nominal composition Bi1.75Pb0.25-xVxSr2Ca2Cu3Oy, x = 0, 0.025, 0.050, 0.075 and 0.1 were fabricated. The influence of the dopant was investigated by x-ray analysis, scanning electron microscopy and electrical resistivity. The results showed both critical temperature and the 2223 phase formations were affected by vanadium and lead concentration. The pure (Bi, Pb) samples showed nearly uniformed homogenous microstructure. More 2223 phase was found in the intermediate ground-pressed sample. The highest critical temperature of 107 K belonged to pure non intermediate ground-pressed (Bi, Pb) sample.